Cutaneous and giant hepatic haemangioma associated with Kasabach-Merritt syndrome in an adult patient with discoid lupus erythematosus - Gao, Wei; Qin, Xihu (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
A 57-year-old female, presented with a dark redness mass with adherent scale and unclear boundaries on the right cheek for 11 years. The patient had complained of swelling and pain of the mass for 2 months. Because of the low platelet count (40–60 × 109/l; norm: 100–300 × 109/l), the patient could not have the skin biopsy of the lesion of the right cheek and was transferred to the inpatient department of haematology for medical treatment. Her past history revealed no other illnesses except that she had bruised easily and suffered from petechiae and ecchymoses of the body frequently for 29 years. The patient was diagnosed as thrombocytopenia by bone marrow biopsy. After being treated with oral steroid therapy, although the platelet count did not return to normal completely, the condition turned better.